2021
DOI: 10.1080/21655979.2021.2010368
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of M2 macrophage-derived extracellular vesicles carrying lncRNA MEG3 in inflammatory responses in ulcerative colitis

Abstract: Ulcerative colitis (UC) is a chronic inflammatory disease of the colon. M2 macrophages possess certain anti-inflammation activity. Accordingly, the current study set out to investigate the potential mechanism of M2 macrophage-derived extracellular vesicles (M2-EVs) in UC inflammation. Firstly, mouse peritoneal macrophages were induced to M2 phenotype, and M2-EVs were isolated. , the murine model of UC was established, and the length and weight of the colon, disease activity index (DAI), apoptosis, and inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…Moreover, Wang et al (2021c) stated that MEG3 might regulate IL-10 expression by targeting miR-98-5p, which may lead to its protective effect against ulcerative colitis (UC). Another study showed how MEG3 alleviated UC inflammation via the miR-206-5p/CREB1 pathway ( Wang et al, 2021d ). Finally, Li et al (2019c) reported that MEG3 may inhibit rheumatoid arthritis through the miR-141/AKT/mTOR signaling pathway ( Figure 2 ).…”
Section: Meg3 In Various Cancersmentioning
confidence: 99%
“…Moreover, Wang et al (2021c) stated that MEG3 might regulate IL-10 expression by targeting miR-98-5p, which may lead to its protective effect against ulcerative colitis (UC). Another study showed how MEG3 alleviated UC inflammation via the miR-206-5p/CREB1 pathway ( Wang et al, 2021d ). Finally, Li et al (2019c) reported that MEG3 may inhibit rheumatoid arthritis through the miR-141/AKT/mTOR signaling pathway ( Figure 2 ).…”
Section: Meg3 In Various Cancersmentioning
confidence: 99%
“…After transfection with plasmids, exosomes rich in miR-590–3p isolated from M2 macrophages inhibited LATS1 expression by activating YAP/β-catenin regulated transcription, which promoted epithelial regeneration and repair of damaged colon. In another research, the LncRNA maternally expressed 3 (MEG3) overexpression lentiviral vector was used to transfect M2 macrophages, and the high expression of MEG3 EVs was obtained after isolation [109] . After drug administration through the tail vein, the MEG3 enters the colon epithelial cells, and competitively binds with mir-20b-5p to promote the transcription of, mir-20b-5p/cAMP responsive element binding protein 1, further enhancing cell vitality and alleviating the inflammatory response of UC.…”
Section: Current Progress Of Exosome‐based Delivery Platform To Treat...mentioning
confidence: 99%
“…M2 macrophages themselves have certain anti-inflammatory activity. MEG3 can regulate the miR-20b-5p/CREB1 axis and induce M2 macrophage-derived extracellular vesicles (M2-EVs) to reduce the inflammatory response ( Wang et al, 2021d ). Upregulation of MEG3 in ulcerative colitis (UC) can enhance the protective effect of M2-macrophage-derived extracellular vesicles (M2-evs) against UC and reduce inflammation ( Wang et al, 2021d ).…”
Section: Functional Mechanismmentioning
confidence: 99%
“…MEG3 can regulate the miR-20b-5p/CREB1 axis and induce M2 macrophage-derived extracellular vesicles (M2-EVs) to reduce the inflammatory response ( Wang et al, 2021d ). Upregulation of MEG3 in ulcerative colitis (UC) can enhance the protective effect of M2-macrophage-derived extracellular vesicles (M2-evs) against UC and reduce inflammation ( Wang et al, 2021d ). MEG3 upregulation in methylene blue (MB)-induced peripheral nerve axons alleviates pain and inflammation associated with obstructive sleep apnea by inhibiting P2X3 protein expression ( Li et al, 2018b ).…”
Section: Functional Mechanismmentioning
confidence: 99%